2013
DOI: 10.3926/ic.370
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la metodología PowerPoint en el aprendizaje de contenidos

Abstract: Purpose: This study focuses on whether the use of PowerPoint technology as the main resource to convey information has an effect on students' learning compared with classes taught without this technology.Design/methodology/approach: The sample consisted of 205 psychology students, divided into four groups, who were taught an ordinary Educational Psychology lesson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The role of the audience is to sit and absorb the information". (Cladellas Pros et al, 2013) observes "the use of technology can have a very positive influence on learning, provided that its use fits the circumstances inherent in learning at any given time, and efficient, flexible resources, like the traditional chalkboard and especially the flexibility and efficiency of a good education professional, are not sacrificed up to blind trust in the technological resource".…”
Section: Background and Review Of The Related Literaturementioning
confidence: 99%
“…The role of the audience is to sit and absorb the information". (Cladellas Pros et al, 2013) observes "the use of technology can have a very positive influence on learning, provided that its use fits the circumstances inherent in learning at any given time, and efficient, flexible resources, like the traditional chalkboard and especially the flexibility and efficiency of a good education professional, are not sacrificed up to blind trust in the technological resource".…”
Section: Background and Review Of The Related Literaturementioning
confidence: 99%
“…PowerPoint is a tool with an extensive use in higher education, and many researchers have studied learning potential related to the use of PowerPoint in lectures (Cladellas Pros, Castelló Tarrida, Badia Martin, & Cirera Amores, 2013;Hashemi, Azizinezhad, & Farokhi, 2012;Savoy, Proctor, & Salvendy, 2009), but students' use of PowerPoint has not received the same attention. Regarding the actual use of PowerPoint among students, in a national survey on the use of ICT in the Norwegian higher education system, the ICT-monitor 2011, 90 % of the students reported that they use "tools for presentation of content", and 29 % said that they used these tools on a weekly basis (Ørnes, Wilhelmsen, Breivik, & Solstad, 2011: 43).…”
Section: Oral Presentationsmentioning
confidence: 99%
“…• the way PPT encourages a fragmentation of information and knowledge, and how this may negatively affect student literacy and thinking (Craig & Amernic, 2006;Tufte, 2006) • limits to the amount of content that can be conveyed per slide, reducing the analytical quality of the information and evidence presented (Cooper, 2009;Tufte, 2006) • the homogenising effect of bullet points, and their distortion of any hierarchical or critical conceptual relationships between ideas (Tufte, 2006;Vallance & Towndrow, 2007) • the tendency towards pre-planned monologues rather than dialogue, leading to teachercentred pedagogy that results in audience/student passivity (Kinchin, Chadha, & Kokotailo, 2008;Pros, Tarrida, Martin, & Amores, 2013) • a reinforcement of student perceptions that they can perform well in exams by studying only the PPT slides, and drops in student attendance in lectures when PPT handouts are available online (Gier & Kreiner, 2009).…”
Section: Powerpoint and Tertiary Teachingmentioning
confidence: 99%
“…There is clear evidence that when lecturers fail to employ interactive and student-centred strategies when using PPT, student learning outcomes reveal no significant difference between students who are taught with PPT and those taught without PPT (Can, Karaca, Akyel, & Demirci, 2012;Pros et al, 2013). On the other hand, more active and student-centred learning in PPT-supported lectures has been shown to be beneficial.…”
Section: Powerpoint and Tertiary Teachingmentioning
confidence: 99%